Polymorphonuclear myeloid-derived suppressor cells regulates immune recovery during HIV infection through PD-L1 and TGF-β pathways - Wang, Zihua; Hu, Yue; Song, Jing; Ma, Ping; Xia, Huan (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundAlthough MDSCs are widely recognized for their immunoinhibitory effects in pathological conditions, their function during HIV infection particularly within the mechanisms underlying incomplete immune recovery remains elusive.MethodsWe conducted a cross-sectional study in which 30 healthy controls and 62 HIV-1-infected subjects [31 immunological non-responders (INRs) and 31 immunological responders (IRs)] were selected. The proportion of MDSCs was determined in each category of participants. Using flow cytometry and real-time PCR, immune regulatory molecules (including PD-L1, ARG1, iNOS, IL-10, TGF-β, and IDO) that are relevant for MDSCs activity were quantified. Furthermore, we investigated the impact of the blockade of PD-L1 and TGF-β pathways on MDSCs and their effects on CD4+ T-cells using in vitro functional experiments.ResultsPMN-MDSCs are more abundant and are negatively correlated to CD4 counts in HIV-infected individuals. In addition, PMN-MDSCs suppress CD4+ T-cell proliferation and IFN-γ production in INRs. Furthermore, correlations were found between PD-L1 expression on PMN-MDSCs and PD-1+ CD4+ T-cells. TGF-β expression on PMN-MDSCs was likewise enhanced in INRs. Importantly, inhibiting both PD-L1 and TGF-β pathways had a synergistic impact on restoring CD4+ T-cell activity in vitro.ConclusionsPMN-MDSCs expansion inhibits CD4+ T-cell responses. We suggest that targeting PD-L1 and TGF-β pathways together may significantly improve immune recovery in INRs.